Peran Kepala Sekolah Dalam Meningkatkan Manajemen Mutu Pendidikan Di Sekolah Dasar Islam Al-Rasyid Pekanbaru - Hamzah Hamzah; Tuti Syafrianti; Bambang Wahyu Susanto; Wismanto Wismanto; Rieskha Tri Adilah. EM (Journal on Education, 2023)
This study aims to find out and describe the role of the principal in improving the quality management of education in Al Rasyid Islamic Elementary School Pekanbaru. This research uses descriptive qualitative methods. The headmaster of Al Rasyid Islamic Elementary School being a main sample in this research. Data collection techniques using the interview, observation and documentation methods. Analysis of research data using reduction techniques, triangulation and conclusions from research data. The results obtained explained that the principal had carried out various efforts and had played a role in improving the quality management of education in Al Rasyid Islamic Elementary School Pekanbaru. Efforts made include various important roles in terms of leadership and also madrasah management both for teachers, students, infrastructure and also supporters of other schools. Conclusion in this study is the role of the principal is very important in improving the management of education quality and the role of the principal has been carried out in various roles; As educators, managers, administrators, supervisors, leaders, innovators and motivators.